The combined effect of bacteriocin-producing Lactobacillus rhamnosus GG-ATCC and Lactoperoxidase system activation on microbiological quality of raw milk with special emphasis against E.coli O157:H7 in milk: Najim Hadi Najim and Farah Ibrahim Mustafa - Najim, Najim Hadi (The Iraqi Journal of Veterinary Medicine, 2017)
Isolates of Enterohaemorrhagic E.coli O157:H7 were isolated from 51 and 41 of locally produced bovine and ovine soft cheese samples. Their identification were confirmed based on the biochemical reactions and both the morphological cultural and serological properties. Presumptive E.coli O157:H7 isolates obtained by using the conventional selective plating on the chromogenic agar were tested further for the presence of both O157 and H7 antigenes using the latex agglutination test antisera. The current microbiological studies revealed that 31 (33.70 %) out of 92 bovine and ovine soft cheese samples were positive for E.coli O157:H7. The highest non significant (P>0.05) prevalence level of E.coli O157:H7 was found in the ewe᾿s soft cheese samples (36.59 %) followed by cow᾿s soft cheese samples (31.37 %). Agar well diffusion bioassay method was used for measuring the antibacterial activity of the crude bacteriocin that was produced by Lactobacillus rhamnosus GG-ATCC against Escherichia coli and the closely related sensitive strains such as L.acidophilus LA-K and L.acidophilus ROO52. The crude bacteriocin that was produced by the L.rhamnosus GG-TACC exhibited significantly (P<0.05) the highest antibacterial potency (100 %) against both the closely related strains of lactobacilli and the stressed E.coli O157:H7 by the activation of the LPS. The activation of the natural LPS of inoculated pasteurized milk had significantly (P<0.05) influenced the inactivation degree of the crude bacteriocin against E.coli O157:H7. There was a significant (P<0.05) reduction in the viable counts of stressed E.coli O157:H7 after each exposure time period (6, 24 and 48 hrs.) to the crude bacteriocin at room storage temperature. An overall conclusion on the basis of the current results pointed out that complete elimination of viable bacterial cells was not achieved neither in the stabilized milk (Activation of LPS) nor after subjecting the stabilized milk to the action of the crude bacteriocin produced by L.rhamnosus GG-ATCC at room storage temperature.